Efficient Task Scheduling Using Constrains Programming - Jung, Soonil; Cho, Jae Bong; Yang, Kyungmo; Kim, Dohun; Kim, Wonjong (Proceedings of IEEE International Symposium on Consumer Electronics, 2025)
This paper introduces a constraint programming algorithm designed for efficient task scheduling in Maintenance, Repair, and Overhaul (MRO) operations, specifically for aircraft engines. By leveraging historical data from Korean Air's MRO maintenance logs, the proposed method achieves optimal scheduling performance by minimizing total maintenance days and maximizing resource utilization. Experimental results reveal an average utilization rate of 99.34%, with some cases reaching 100%. Furthermore, this study explores the potential application of the algorithm in consumer electronics manufacturing, emphasizing its adaptability to various industrial environments. The findings highlight the algorithm's ability to optimize resource allocation, reduce operational downtime, and enhance scheduling efficiency, paving the way for broader industrial applications.